2023
DOI: 10.1177/01423312221141755
|View full text |Cite
|
Sign up to set email alerts
|

Gas sensing properties of a maghemite-coupled porphyrin thin film–based optical waveguide sensor

Abstract: This study concerns the development of a maghemite (γ-Fe2O3)-coupled tetra sulfophenyl porphyrin (TSPP) thin film–based optical waveguide (OWG) sensor (TSPP-γ-Fe2O3-OWG) for the detection of ethylenediamine (EDA). For ease of manufacture, we fabricated sensors using a spin-coating technique, and characterized their response based on their ultraviolet-visible (UV-vis) absorption spectra and the response intensity of OWG sensor. We have observed significant changes in the location of the peaks in the sensor’s UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Iron oxide, commonly known as hematite (α-Fe 2 O 3 ), magnetite (Fe 3 O 4 ), and/or maghemite (γ-Fe 2 O 3 ), offers several benefits, including chemical and biological stability, low toxicity, a superparamagnetic characteristic, and low cost for large-scale synthesis that make it well suited for sensor applications . The choice of the shell material and its properties are critical considerations to achieve the desired performance and functionality of the Fe 2 O 3 nanoparticles in biomedical imaging, drug delivery, magnetic separation, environmental remediation, and catalysis applications . Au, MoS 2 , MnO 2 , SiO 2 , ZnO, and TiO 2 have all been used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron oxide, commonly known as hematite (α-Fe 2 O 3 ), magnetite (Fe 3 O 4 ), and/or maghemite (γ-Fe 2 O 3 ), offers several benefits, including chemical and biological stability, low toxicity, a superparamagnetic characteristic, and low cost for large-scale synthesis that make it well suited for sensor applications . The choice of the shell material and its properties are critical considerations to achieve the desired performance and functionality of the Fe 2 O 3 nanoparticles in biomedical imaging, drug delivery, magnetic separation, environmental remediation, and catalysis applications . Au, MoS 2 , MnO 2 , SiO 2 , ZnO, and TiO 2 have all been used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“… 14 The choice of the shell material and its properties are critical considerations to achieve the desired performance and functionality of the Fe 2 O 3 nanoparticles in biomedical imaging, drug delivery, magnetic separation, environmental remediation, and catalysis applications. 15 Au, 16 MoS 2 , 17 MnO 2 , 18 SiO 2 , 19 ZnO, 20 and TiO 2 21 have all been used for this purpose. Ahadpour Shal et al reported that the coprecipitation technique was used to make core–shell-type magnetite Fe 3 O 4 @ZnO nanostructures.…”
Section: Introductionmentioning
confidence: 99%